Depressive disorders in family members of patients diagnosed with chronic schizophrenia - Tsirigotis, Konstantinos; Gruszczyński, Wojciech; Krawczyk, Barbara (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. The disease of a family member constitutes a difficult situation, requiring activating of coping mechanisms not only in the ill person, but often also in the other members. The situation is becoming even more difficult, if it is a psychosis and in addition a chronic one; disease may constitute strain (stress) or even overstrain (distress) not only for the patient, but also for his family and his close ones. Aim of the study. The main aim of the work was the assessment of depressive disorders among the carers of patients having chronic schizophrenia. Material and methods. The research was carried out among 100 adults who permanently look after a chronically schizophrenic member of their families. In the research there was used Beck Depression Inventory Scale. Results. The examined people experienced emotional disorders (e.g. reduced mood), intellectual disorders (like concentration, attention and sleeping problems). The carers were exposed to lengthy stress and in most cases they themselves took advice from professionals. The research resulted in the fact that carers of schizophrenic people suffered themselves from somatic and psychological ailments for a longer time. According to Beck Depression Scale the level of moderate-severe depression appeared in 60% of examined, soft depression in 28% and severe depression developed in 7% of the women. The intensification of depression was generally found in 95% of cases and only 5% of the examined did not show any symptoms. Among the psychological symptoms there dominated the most: the sense of insufficiency (49%), inability to work (43%), the lack of satisfaction (35%), over-sensitivity (35%), calling for help (34%) and reduced mood (33%). The somatic symptoms appearing in the examined people are the following: fatigue (44%), somatic disorders (35%), a distorted view of one’s body (34%), sleep disorders (30%). Conclusions. Looking after a member of one’s family is very difficult. This is a great burden for carers and this lead to depressive disorders. To take care of a patient the carers must have complex knowledge and psychological support. Depressive disorders, in people who takes care of patients suffering from chronic schizophrenia, are an important issue connected with health and social problems. Nursing Topics 2010; 18 (4): 469-476